DRAMATURGICAL THEORY OF HYPNOSIS - Pérez Álvarez, Marino (Anales de Psicología / Annals of Psychology, 1999)
An explanation of hypnosis in terms of theatre is proposed. In this respect, the dramatic structure of the hypnotic procedure is analysed. It can be observed that hypnosis follows the proceeding of the role enactment. More specifically, the interpretation of the hypnotic role is considered, both in terms of social representation and private experience. The notion of self-deception is introducted and the gigure of theatre as a metaphor of the therapy is climed.